EKOLOGI SEBAGAI JEMBATAN DIALOG UMAT ANTARAGAMA - Pappalan, Abialtar Altar (Universitas Sanata Dharma, 2024)
The relationship between religious communities, especially in Indonesia, is very dynamic. This cannot be separated from the fact that the level of tolerance among religious communities in Indonesia can be greatly influenced by several factors, one of which is politics, as it is stated by the Ministry of Religious Affairs. Therefore, Indonesian society needs to constantly strive to maintain harmony within the community. The purpose of this writing is to explore the importance of a bridge of dialogue among religious communities in promoting harmony. The bridge of dialogue in question is the issue of ecology, such as forest fires, environmental pollution, illegal logging, and so on. The research method used in this paper is literature study, which involves reading, taking notes, and examining various readings relevant to the topic, and then placing them within the theoretical framework based on the thinking of Stanlay J. Samartha about Pneumatology Religionum and the mutualization model of Paul Knitter. The results show that there is a bridge in the form of a common understanding of ecology as God's creation, and it is the responsibility of all religious communities to preserve it together.Abstrak Hubungan umat beragama khususnya di Indonesia sangatlah dinamis. Hal ini tidak dapat terlepas dari kenyataan yang dikemukakan oleh Kemenag bahwa tingkat toleransi antar umat agama di Indonesia bisa sangat dipengaruhi oleh beberapa keadaan, salah satunya politik. Oleh sebab itu, masyarakat Indonesia perlu selalu mengupayakan dan menjaga kerukunan dalam masyarakat. Tujuan tulisan ini adalah menggali pentingnya sebuah jembatan dialog antar umat beragama dalam mengupayakan kerukunan. Jembatan dialog yang dimaksud adalah masalah ekologi yang sedang dihadapi, misalnya pembakaran hutan, pencemaran lingkungan, penebangan liar, dan lain sebagainya. Metode penelitian yang digunakan dalam tulisan ini studi kepustakaan, yaitu dengan cara membaca, mencatat serta menelaah berbagai bacaan yang sesuai dengan pokok yang dibahas, kemudian menempatkannya dalam kerangka berpikir teoritis berdasarkan pemikiran Stanlay J. Samartha tentang Pneumatologi Religionum dan kerangka berpikir model mutualisasi Paul Knitter. Hasilnya menunjukkan bahwa ada jembatan berupa pemahaman yang sama terhadap ekologi sebagai ciptaan Tuhan dan menjadi tugas semua umat beragama memeliharanya sebagai tanggung jawab bersama.